Digitalisasi Pembelajaran PIAUD: Inovasi Media Islami di Era 5.0 - Mayang Sari Lubis (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study aims to describe the forms of learning digitalization in Islamic Early Childhood Education (PIAUD) during the society 5.0 era and to analyze Islamic media innovations that support the learning process. This research employs a qualitative method with a library research approach, focusing on literature analysis related to learning digitalization and the implementation of Islamic values in early childhood education. The results indicate that digitalization has a positive impact on children’s interest and understanding through the use of digital media such as Omar & Hana animations, Nussa Rara, Muslim Kids TV applications, Marbel Mengaji educational games, the Kiddyfun platform, the AVOID game, and Augmented Reality (AR) technology. These media effectively integrate Islamic values in an engaging and interactive manner. However, challenges include limited infrastructure, insufficient teacher competence in digital literacy, and inadequate supervision of children’s gadget use. Therefore, collaboration between the government, educational institutions, and families is essential to develop Islamic media innovations that align with children’s developmental needs and the demands of the digital era.